Effect of aspirin on the diagnostic accuracy of the faecal immunochemical test for colorectal advanced neoplasia. Issue 1 (February 2018) - Bujanda, Luis; Sarasqueta, Cristina; Vega, Pablo; Salve, María; Quintero, Enrique; Alvarez-Sánchez, Victoria; Fernández-Bañares, Fernando; Boadas, Jaume; Campo, Rafel; Garayoa, Ana; Ferrandez, Angel; Torrealba, Leyanira; et al.
Background: Aspirin (ASA) is a drug that can cause gastrointestinal lesions and symptoms. Colorectal cancer (CRC) is the most prevalent type of cancer in Western countries. We assessed the effect of aspirin on the diagnostic accuracy of the faecal immunochemical test (FIT) for CRC and/or advanced neoplasia (AN) in patients undergoing colonoscopy for gastrointestinal symptoms. Methods: We conducted a prospective multicentre observational study of diagnostic tests that included patients with gastrointestinal symptoms undergoing colonoscopy between March 2012 and 2014 (the COLONPREDICT study). Symptoms were assessed and a FIT and blood tests assessing haemoglobin and carcinoembryonic antigen (CEA) levels were performed. Results: The study included 3052 patients: A total of 2567 did not take aspirin (non-user group) and 485 (16%) took aspirin (user group). Continuous treatment with ASA did not change the AUC (0.88, 0.82; p = 0.06), sensitivity (92%, 88%; p = 0.5) or specificity (71%, 67%; p = 0.2) of the FIT for CRC detection. Similarly, we found no differences in the AUC (0.81, 0.79; p = 0.6), sensitivity (74%, 75.5%; p = 0.3) or specificity (76%, 73.6%; p = 0.3) for AN detection. Patients with an aspirin use of ≥ 300 mg/day had a lower prevalence of AN and the sensitivity, specificity and AUC for AN for these patients were 54%, 68% and 0.66, significantly lower than for the non-user group ( p = 0.03). Conclusions: Aspirin does not modify the diagnostic accuracy of FIT for CRC and/or AN in patients with gastrointestinal symptoms. Aspirin use of ≥ 300 mg/day decreases the accuracy of the test.